2011
DOI: 10.1108/17410391111097401
|View full text |Cite
|
Sign up to set email alerts
|

How can teleworking be pro‐poor?

Abstract: Purpose -The purpose of the paper is to examine evidence in order to discover if teleworking has a pro-poor growth impact -reducing inequality. For this reason, the paper seeks to propose a telework taxonomy for the poor and research questions that trigger future empirical research on poor teleworkers. Design/methodology/approach -The paper's approach is a literature review. The focused literature includes articles that analyze telework issues with a potential for the poor. Such issues are mainly workforce and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 64 publications
0
37
0
2
Order By: Relevance
“…This flexibility can contribute to organisational agility, as workers are able to access work related information more efficiently, regardless of time and space (Morgan, ; Campbell and McDonald, ; Overmyer, ). Increased flexibility and autonomy for workers are seen as an aspect contributing to higher job satisfaction (Morgan, ; Gajendran and Harrison, ; Golden, ; Hornung and Glaser, ; Fonner and Roloff, ; Overmyer, ), improved work morale (Campbell and McDonald, ; Kanellopoulos, ; Pyöriä, ; Wheatley, ) and a corporate image of a flexible workplace caring about its employees (Baruch, ). Furthermore, several studies argue that the flexibility enabled by telework can improve workers ability to better coordinate work and non‐work commitments, thus improving work‐life balance (Sullivan and Lewis, ; Gajendran and Harrison, ; Golden, ; Gregg, ; Kanellopoulos, ; Overmyer, ; Tremblay and Thomsin, ).…”
Section: Outcomes and Paradoxes In Findings Of Earlier Telework Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This flexibility can contribute to organisational agility, as workers are able to access work related information more efficiently, regardless of time and space (Morgan, ; Campbell and McDonald, ; Overmyer, ). Increased flexibility and autonomy for workers are seen as an aspect contributing to higher job satisfaction (Morgan, ; Gajendran and Harrison, ; Golden, ; Hornung and Glaser, ; Fonner and Roloff, ; Overmyer, ), improved work morale (Campbell and McDonald, ; Kanellopoulos, ; Pyöriä, ; Wheatley, ) and a corporate image of a flexible workplace caring about its employees (Baruch, ). Furthermore, several studies argue that the flexibility enabled by telework can improve workers ability to better coordinate work and non‐work commitments, thus improving work‐life balance (Sullivan and Lewis, ; Gajendran and Harrison, ; Golden, ; Gregg, ; Kanellopoulos, ; Overmyer, ; Tremblay and Thomsin, ).…”
Section: Outcomes and Paradoxes In Findings Of Earlier Telework Researchmentioning
confidence: 99%
“…While these developments for telework in practice are puzzling, research on telework implications is even more so. Studies that demonstrated positive outcomes from telework, such as improved work‐life balance for employees and reduced costs for organisations (Gregg, ; Kanellopoulos, ), are contrasted by other studies demonstrating potentially negative outcomes, such as difficulties in developing shared knowledge among employees and reduced work satisfaction (Pyöriä, ; Sarker et al ., ). Particularly paradoxical are contradictory findings where telework is reported to be positive for one aspect in some studies, such as improved work‐life balance, whereas in others it is reported to be negative and related to increased work‐life conflict (Jarvenpaa and Lang, ; Gajendran and Harrison, ; Sorensen, ; Wheatley, ).…”
Section: Introductionmentioning
confidence: 97%
“…The findings from investigations of the impact of telework on workload and work related pressures are also mixed. While telework can be seen as a way of alleviating a high workload and work related stress for some teleworkers (Baruch, 2001;Kanellopoulos, 2011), it may also increase organizational stress and workload for all employees (Bailey and Kurland, 2002). Table 3 presents the three outcomes identified from the literature relating to workload and work/home-life balance.…”
Section: Workload and Work/home-life Balancementioning
confidence: 99%
“…Estudos sugerem que, em níveis de realização da tarefa, o teletrabalho proporciona um aumento da flexibilidade sobre onde e quando o trabalhador efetivamente realizará o seu trabalho (Boell et al, 2013), possibilitando uma diminuição no tempo gasto em deslocamentos e custos para tal (Kanellopoulos, 2011). Também existem resultados de pesquisas que mostram o teletrabalho como uma modalidade que abarca atividades mais complexas, as quais exigem conhecimentos especializados e altos níveis de instrução.…”
unclassified
“…No teletrabalho, o empregado geralmente executa suas atividades em um ambiente doméstico, longe da organização (Golden & Gajendran, 2018). A literatura sugere que essa alternativa proporciona benefícios, uma vez que torna possível a conciliação das responsabilidades profissionais com as necessidades pessoais e familiares (Gajendran & Harrison, 2007;Kanellopoulos, 2011;Raghuram & Wiesenfeld, 2004). Contudo, é necessário considerar que as relações que os indivíduos desenvolvem com seus colegas, subordinados e supervisores no ambiente organizacional são fatores importantes que moldam e dão sentido à experiência de trabalho (Chiaburu & Harrison, 2008).…”
unclassified